Classics@ (Harvard University, Center for Hellenic Studies, 2002)
"Each issue is meant to be not static but dynamic, continuing to evolve with interaction from its readers as participants. New issues will appear when the editors think there is good material to offer."
Gesehen am 28.09.2022
Keywords: Zeitschrift